The Appropriate Use of Neurostimulation of the Spinal Cord and Peripheral Nervous System for the Treatment of Chronic Pain and Ischemic Diseases: The Neuromodulation Appropriateness Consensus Committee. Issue 6 (August 2014) - Deer, Timothy R.; Mekhail, Nagy; Provenzano, David; Pope, Jason; Krames, Elliot; Leong, Michael; Levy, Robert M.; Abejon, David; Buchser, Eric; Burton, Allen; Buvanendran, Asokumar; Candido, Kenneth; et al.
<x xml:space="preserve">Abstract</x> Introduction The Neuromodulation Appropriateness Consensus Committee (NACC) of the International Neuromodulation Society (INS) evaluated evidence regarding the safety and efficacy of neurostimulation to treat chronic pain, chronic critical limb ischemia, and refractory angina and recommended appropriate clinical applications. Methods The NACC used literature reviews, expert opinion, clinical experience, and individual research. Authors consulted the Practice Parameters for the Use of Spinal Cord Stimulation in the Treatment of Neuropathic Pain (2006), systematic reviews (1984 to 2013), and prospective and randomized controlled trials (2005 to 2013) identified through PubMed, EMBASE, and Google Scholar. Results Neurostimulation is relatively safe because of its minimally invasive and reversible characteristics. Comparison with medical management is difficult, as patients considered for neurostimulation have failed conservative management. Unlike alternative therapies, neurostimulation is not associated with medication‐related side effects and has enduring effect. Device‐related complications are not uncommon; however, the incidence is becoming less frequent as technology progresses and surgical skills improve. Randomized controlled studies support the efficacy of spinal cord stimulation in treating failed back surgery syndrome and complex regional pain syndrome. Similar studies of neurostimulation for peripheral neuropathic pain, postamputation pain, postherpetic neuralgia, and other causes of nerve injury are needed. International guidelines recommend spinal cord stimulation to treat refractory angina; other indications, such as congestive heart failure, are being investigated. Conclusions Appropriate neurostimulation is safe and effective in some chronic pain conditions. Technological refinements and clinical evidence will continue to expand its use. The NACC seeks to facilitate the efficacy and safety of neurostimulation.